HCV-infected individuals have higher prevalence of comorbidity and multimorbidity: a retrospective cohort study - Cooper, Curtis L; Galanakis, Chrissi; Donelle, Jessy; Kwong, Jeff; Boyd, Rob; Boucher, Lisa; Kendall, Claire E (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Almost 1% of Canadians are hepatitis C (HCV)-infected. The liver-specific complications of HCV are established but the extra-hepatic comorbidity, multimorbidity, and its relationship with HCV treatment, is less well known. We describe the morbidity burden for people with HCV and the relationship between multimorbidity and HCV treatment uptake and cure in the pre- and post-direct acting antiviral (DAA) era. Methods We linked adults with HCV at The Ottawa Hospital Viral Hepatitis Program as of April 1, 2017 to provincial health administrative data and matched on age and sex to 5 Ottawa-area residents for comparison. We used validated algorithms to identify the prevalence of mental and physical health comorbidities, as well as multimorbidity (2+ comorbidities). We calculated direct age- and sex-standardized rates of comorbidity and comparisons were made by interferon-based and interferon-free, DAA HCV treatments. Results The mean age of the study population was 54.5 years (SD 11.4), 65% were male. Among those with HCV, 4% were HIV co-infected, 26% had liver cirrhosis, 47% received DAA treatment, and 57% were cured of HCV. After accounting for age and sex differences, the HCV group had greater multimorbidity (prevalence ratio (PR) 1.38, 95% confidence interval (CI) 1.20 to 1.58) and physical-mental health multimorbidity (PR 2.71, 95% CI 2.29–3.20) compared to the general population. Specifically, prevalence ratios for people with HCV were significantly higher for diabetes, renal failure, cancer, asthma, chronic obstructive pulmonary disease, substance use disorder, mood and anxiety disorders and liver failure. HCV treatment and cure were not associated with multimorbidity, but treatment prevalence was significantly lower among middle-aged individuals with substance use disorders despite no differences in prevalence of cure among those treated. Conclusion People with HCV have a higher prevalence of comorbidity and multimorbidity compared to the general population. While HCV treatment was not associated with multimorbidity, people with substance use disorder were less likely to be treated. Our results point to the need for integrated, comprehensive models of care delivery for people with HCV.